PSYCHOLOGICAL APPROACHES OF IMPROVEMENT OF THE EFFICIENCY OF COMMUNICATION IN THE CONDITIONS OF ANTI-CRISIS MANAGEMENT - Vovk N. P.; Diachkova O. M.; Mokhnar L. I. (International Journal of Innovative Technologies in Social Science, 2021)
The psychological approaches for improvement of efficiency of organization and communication in anti-crisis management, based on the explication of the concepts “crisis situation”, “anti-crisis management”, “social communication”, “communication in a crisis”, as well as based on the analysis of the application of theories and models of communication in management in emergencies are defined in the article.